The Sociological Perspective on Maghi Festival as the New Year of the Tharu Community - Pathak, Jagat Raj (NPRC Journal of Multidisciplinary Research, 2024)
The Tharu are an indigenous community living in the Terai and inner Terai regions of Nepal, which is known for its diverse caste, ethnicity, language, social structures, culture, and religions. Maghi is the main festival of the Tharu community. The present research paper clarifies the relevance of Maghi festivals. In this paper customs, procedures and celebration of Maghi are examined. The present study uses a combination of exploratory and descriptive research designs and is based on interviews with elders, ritual performers, and educated members of the Tharu community. Tharu people celebrate Maghi as the New Year, marked by the government has declared holidays. The festival, lasting seven days, involves cleaning, refurbishing houses, and cultural activities. Rituals include holy baths, prayers for children, and offering to deities. It fosters community bonds, while its culinary traditions highlight cultural significance. Economic, social, and cultural factors have contributed to the dynamic nature of Maghi practices, A sociological study by concentrating on the Maghi festival as Tharu new year of study area Birendranagar Municipality-9, Patalganga village, Surkhet. It offers particular insights into Maghi festival's importance, practices and gradually changing to reflect qualities that are inconsistent with modern morals.